Electronic evidence as an object of forensic doctrine on crime traces - Karaman, Kostiantyn (Archives of Criminology and Forensic Sciences, 2025)
It is noted that currently the criminal procedural legislation of Ukraine does not provide a clear and comprehensive definition of electronic evidence, does not establish its characteristic features, the limits of permissible use and the procedural procedure for dealing with it. Such a regulatory vacuum complicates the activities of all participants in criminal proceedings — investigators, prosecutors, defense attorneys, judges — and creates significant obstacles to effective proof. In practice, this leads to the fact that electronic evidence is often recognized as inadmissible precisely due to non-compliance with the procedures for its removal, fixation or examination, which subsequently negatively affects the legality and validity of court decisions. This article purpose is to substantiate the feasibility of introducing electronic evidence into the system of objects of forensic science on traces of crime, to clarify its nature, specific features, place in the system of forensic objects, as well as to substantiate the need to integrate the category of electronic trace into modern investigative practice and forensic theory. The article explores the issue of electronic evidence as a new object of forensic science on traces of crime. It is substantiated that digital images, despite their intangible nature, are traces of crime in the forensic sense. Modern approaches to electronic evidence in the EU legal systems are analyzed, and regulatory initiatives for their regulation are outlined. The author emphasizes the need to recognize electronic evidence as a separate procedural source, its integration into forensic theory and the development of appropriate research methods. The conclusion is made about the expediency of harmonizing national legislation with European standards of digital forensics.